Diseño e implementación de un módulo electromecánico para la rehabilitación física de la mano derecha afectada como secuela de un ataque cerebrovascular - Criollo Paredes, Carlos Andrés; López Pantoja, David Eduardo; Jojoa Acosta, Mario Fernando (Universidad y Salud, 2012)
The designed rehabilitation moduleis a system compound by electronic circuits to automate and control a robotic orthotic for a hand. It cooperates in the upper limb rehabilitation in the right distal zone of hemiparetic stroke patients. The motion intention is detected by a noninvasive electronic electromyography system using sensors (surface electrodes) placed in skin surface to report electrical activity of a single muscle. An instrumentation circuit is disigned for signal processing of acquired signals based on low voltage bio-signals tretment. A latest digital processing section identifies the kind of movement. When the patient moves his or herafected hand, the out of the system presents and amplified electromyography signal without noise components that is used like a control signal in the actuators of automated robotic orthotics for the right hand. The designed divice contains flexion and extension exercises of the right hand and extension and opposition of the thumb.